EFFECT OF MUMIYO (SHILAJIT) ON INTRAVASCULAR FLUID VOLUME AND PLASMA ELECTROLYTE BALANCE IN RATS - Boltabaeva Dilbarkhon Fayzirakhmanovna; Rizakova Dilorom Pulatovna (Western European Studies, 2025)
This study investigated the effect of mumiyo (shilajit) on intravascular fluid volume and plasma electrolyte balance in rats. Adult laboratory rats were divided into control and experimental groups. The experimental group received mumiyo orally at a dose of 50 mg/kg daily for seven days. Parameters such as intravascular fluid volume and plasma concentrations of sodium, potassium, and calcium were measured. The administration of mumiyo did not significantly affect any of the studied indicators compared with the control group (P > 0.05). These results suggest that short-term oral administration of mumiyo does not alter basic fluidelectrolyte homeostasis in healthy rats
Keywords: Traditional medicine; mumiyo; shilajit; historical ethnomedicine